2019
DOI: 10.2337/dc18-2156
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Proximal and Distal Small Intestinal Glucose Exposure on Glycemia, Incretin Hormone Secretion, and the Incretin Effect in Health and Type 2 Diabetes

Abstract: Cells releasing glucose-dependent insulinotropic polypeptide (GIP) and glucagonlike peptide 1 (GLP-1) are distributed predominately in the proximal and distal gut, respectively. Hence, the region of gut exposed to nutrients may influence GIP and GLP-1 secretion and impact on the incretin effect and gastrointestinal-mediated glucose disposal (GIGD). We evaluated glycemic and incretin responses to glucose administered into the proximal or distal small intestine and quantified the corresponding incretin effect an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 39 publications
(48 reference statements)
0
37
2
Order By: Relevance
“…Metformin has been shown to reduce glucose absorption in the upper small intestine 11 and bile acid resorption in the ileum. 13 The resulting increase in the exposure of glucose 31 and/or bile acid 32,33 to more distal regions of the gut would favour enhanced GLP-1 secretion following oral glucose. In the present study, it is possible that proximal metformin administration was more prominent in inhibiting glucose absorption, 11 Along with the stimulation of GLP-1 secretion, there was a treatment effect of metformin on the rate of GE, such that proximal metformin infusion slowed GE substantially, and distal metformin administration tended to do so.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin has been shown to reduce glucose absorption in the upper small intestine 11 and bile acid resorption in the ileum. 13 The resulting increase in the exposure of glucose 31 and/or bile acid 32,33 to more distal regions of the gut would favour enhanced GLP-1 secretion following oral glucose. In the present study, it is possible that proximal metformin administration was more prominent in inhibiting glucose absorption, 11 Along with the stimulation of GLP-1 secretion, there was a treatment effect of metformin on the rate of GE, such that proximal metformin infusion slowed GE substantially, and distal metformin administration tended to do so.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, exendin (9–39) was associated with an early, albeit modest, increase in plasma total GIP. Since GLP‐1 accounts for the slowing of gastric emptying and small intestinal transit, the so‐called “ileal brake”, antagonism of GLP‐1 may have resulted in an increase in the transit of fat within the proximal small intestine and therefore stimulated additional GIP secretion – our recent study in both healthy people and people with T2DM has shown that the distal small intestine is also capable of secreting GIP …”
Section: Discussionmentioning
confidence: 99%
“…Two people withdrew prior to the first study visit, and three withdrew before completing the study owing to intolerance of the nasoduodenal catheter (n = 2) or the intraduodenal fat infusion (n = 1, on the placebo/saline day). Accordingly, 15 participants (10 men and five women, mean age 68.8 ± 2.2 years, body mass index 30.2 ± 1.3 kg/m, glycated haemoglobin 49.3 ± 2.1 mmol/mol [6.7 ± 0.2%], and duration of known diabetes 6.6 ± 1.5 years) completed the study and were included in the final analysis. None had impaired liver or renal function, had diabetic microvascular complications, was a smoker, or was taking medication known to affect gastrointestinal function.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported that metformin induced GLP‐1 secretion ex vivo in human gut mucosa, suggesting the potential for metformin to stimulate GLP‐1 secretion directly . If this were the case, infusing metformin into the distal small intestine, where GLP‐1‐releasing L‐cells are abundant, would be anticipated to enhance GLP‐1 secretion (as is evident with other GLP‐1 stimuli, such as glucose); however, there was no difference in the effects of metformin (1 g) administered into the ileum compared to metformin administered into the duodenum on GLP‐1 secretion, gastric emptying or the glycaemic response to oral glucose in patients with T2DM (Figure ) . These observations suggest that stimulation of GLP‐1 secretion by metformin is mediated by indirect mechanisms.…”
Section: Gastrointestinal Effects Of Metformin: Role Of Gut Peptidesmentioning
confidence: 99%